TOTAL DEFENCE: A NECESSARY BUT STILL NONEXISTENT GROUND OF THE SERBIAN DETERRENCE STRATEGY - Jovanović, Miloš (Politeia, 2026)
As a militarily neutral state, Serbia has to rely on internal balancing in order to attain an effective deterrence strategy. Therefore, all the strategic documents of the Republic of Serbia – the National Security Strategy and the Defence Strategy – have defined the concept of total defence as a goal to achieve. Although significant steps have been realized in that complex undertaking – and notably the effort of the theoretical and normative elaboration of the concept – Serbia still faces many challenges of various kind in order to transform the concept of total defence into a set of practical and concrete measures that will constitute the foundation of the Serbian deterrence and help the country in the preservation and defence of its national interests. One of the problems resides in the fact that the understanding of the concept of total defence seems to be excessively narrow. By limiting the scope of total defence to its two classical components – the military defence on one hand and the civil defence on the other – a wide palette of measures and actions has been put aside and possible threats ignored. The question of possible cultural or ideological threats remained untackled and the idea of overall or comprehensive defence that would, for example, include spiritual defence, stayed completely out of range of the policy makers. But even with regard to the narrow understanding of the concept of total defence, some key elements are still missing, such as the mandatory military service or a full normative elaboration of the civil defence, let alone its practical implementation. Besides these problems, there is a more fundamental issue concerning the existence of necessary requirements for a successful total defence policy since internal balancing cannot be solely seen as the need for increasing military capacities. Moreover, it is a widely accepted theoretical concept today that internal balancing implies elements such as the strength and efficiency of state institutions, political stability, and social cohesion. Having this in mind, the particular context of Serbia – with a deficient democratic regime, political instability, institutional ineffectiveness, and a weakened social cohesion – is not a fertile ground for developing the concept of total defence. Finally, the most important challenge that Serbia is facing and that will determine the faith of both the military neutrality and the total defence that derives from it is the need of making a choice and of having a coherent foreign policy, which is, for the moment, still marked by contradictory goals of preserving the territorial integrity of the country and joining the European Union. If the final choice is made in favour of the EU accession – which necessarily means the acceptance of the secession of Kosovo and Metohija, it is more than likely that the strategic decision of the military neutrality will cease to exist since it will lose its main sense of purpose.